2020
DOI: 10.1097/cnq.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Cardiovascular System

Abstract: COVID-19, a symptom complex of respiratory failure induced by a highly infectious pathogen, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has been classified as a pandemic. As of April 15, 2020, there have been 2 million people diagnosed with the viral infection and 130 000 deaths globally. It is highly likely that the number of infections is underrepresented secondary to variations in testing and reporting strategies globally. In this short review, we aim to summarize the current understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…4,7,12 has been shown to be associated with development of cardiovascular conditions, including myocardial injury, arrhythmia, acute coronary syndrome, and venous thromboembolism. 5,6,10,11,[13][14][15][16][17] Although early data relating to pediatric COVID-19 cases are limited, systematic reviews of cases in children showed that underlying cardiovascular defects were prevalent, with congenital heart disease (CHD) being associated with worse clinical outcomes. 18,19 Congenital heart disease is estimated to occur in 3 to 10 children per 1000 live births in the US, [20][21][22] and this rate is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…4,7,12 has been shown to be associated with development of cardiovascular conditions, including myocardial injury, arrhythmia, acute coronary syndrome, and venous thromboembolism. 5,6,10,11,[13][14][15][16][17] Although early data relating to pediatric COVID-19 cases are limited, systematic reviews of cases in children showed that underlying cardiovascular defects were prevalent, with congenital heart disease (CHD) being associated with worse clinical outcomes. 18,19 Congenital heart disease is estimated to occur in 3 to 10 children per 1000 live births in the US, [20][21][22] and this rate is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the severity of SARS infection largely relied on the load of virus as well as immunopathological response of host according to the accumulative evidence [43]. The common imbalance of Th1 and Th2 response easily contributed to cytokine storm which may be linked with myocardial injury [44]. Cardiac troponin T may be a sensitive marker help us discern severe patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the fundamental mechanism by which SARS-CoV-2 interacts with CD147 in humans is debated in the scientific community [ 13 ], there is a lot of potential rationales supporting the theory that CD147 could still play a role in the COVID-19 clinical course, even if it is not a functional viral entry receptor. For example, compared to ACE2 protein expression, CD147 is expressed in cardiomyocytes and endothelial cells, which may correlate with massive hemodynamic instability and cardiovascular abnormalities during SARS-CoV-2 infection [ 14 , 15 ]. The high expression of CD147 protein, but not ACE2 protein, on erythrocytes and platelets, may also contribute to a "catch and clump” mechanism that increases the risk of thrombosis in various organ systems during SARS-CoV-2 infection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%